TANBA-SPHINCS+ - POST-QUANTUM CRYPTOGRAPHIC HASH-BASED DIGITAL SIGNATURE ALGORITHM - Ospanov Р.М.; Seitkulov Е.Н.; Yergaliyeva Б.Б.; Utebayev К.А.; Atanov С.К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The paper considers the TANBA-SPHINCS+ digital signature algorithm, which is a modification of the SPHINCS+ post-quantum hash-based scheme. The algorithm uses the TANBA cryptographic hash function developed on the basis of a modified Sponge scheme, where instead of one internal function, many internal functions with a pseudo-random choice of their sequence are used. This approach provides increased resistance to cryptanalytic attacks and adaptability to various security and performance requirements. TANBA-SPHINCS+ retains the key properties of SPHINCS+, including resistance to quantum attacks and independence from complex cryptographic assumptions. The new scheme opens up additional opportunities for building reliable post-quantum digital signature systems.